PSYCHOLOGICAL ASPECTS OF EVALUATION OF QUALITY OF TRAINING OF SPECIALISTS IN INSTITUTIONS OF PROFESSIONAL PREVIOUS EDUCATION IN TODAY'S CONDITIONS (Innovative professional education, 2022)
Psychological aspects of the process of assessing the quality of training in professional previous institutions in wartime should be an important element of adaptation, stabilization of mental states and socialization of students.
Keywords: professional previous education; assessment; martial law; applicants; psychological aspects of assessment